2013
DOI: 10.2460/javma.243.8.1162
|View full text |Cite
|
Sign up to set email alerts
|

Superficial digital flexor tendonitis in cutting horses: 19 cases (2007–2011)

Abstract: The location of SDF tendonitis in cutting horses appeared to be unique in that no central core lesions were detected ultrasonographically. Lesions at the periphery of the tendon may have an increased ability to heal, compared with lesions at the central core. Results suggested that cutting horses with SDF tendonitis have a better prognosis than that reported for affected racehorses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Western performance includes reining, cutting, roping, barrel, among others, and the predominant breed used is the American Quarter Horse (DABAREINER et al, 2005;SCOTT, 2008;TIPTON et al, 2013), the same was observed in this study. During barrel racing, the horse performs a Site of injury clover leaf pattern at gallop around three barrels.…”
Section: -------Dressage--------------racing------------polo Pony----supporting
confidence: 82%
See 1 more Smart Citation
“…Western performance includes reining, cutting, roping, barrel, among others, and the predominant breed used is the American Quarter Horse (DABAREINER et al, 2005;SCOTT, 2008;TIPTON et al, 2013), the same was observed in this study. During barrel racing, the horse performs a Site of injury clover leaf pattern at gallop around three barrels.…”
Section: -------Dressage--------------racing------------polo Pony----supporting
confidence: 82%
“…Sport and training program influence the prevalence and predispose musculoskeletal injuries and lameness in horses (EVANS & WALSH, 1997;MURRAY et al, 2006;MENARIM et al, 2012;TIPTON et al, 2013), depending on the work overload on specific anatomical structures also related to the type of sport and level of training (MURRAY et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of peripheral tendon lesions has not been investigated separately. However, it has been assumed that these lesions typically occur in show jumpers, dressage horses [52] and cutting horses [53]. They may be attributed to degeneration or blunt trauma, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They may be attributed to degeneration or blunt trauma, e.g. self-kicking with the ipsilateral hind hoof, or to excessive strain on the lateral aspect of the affected limbs [53]. By contrast centrally located (“core”) lesions are the result of repetitive micro-injuries at high speed exercise and consecutive repair with insufficient tissue [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation